Pengaruh PAD terhadap PDRB dan Belanja Modal Kabupaten/ Kota di Provinsi Bali - Hariyadi, Eko; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 12, Desember 2014 (pp. 549-623), 2014)
One of the main indicators to measure the performance of regional economic development is the growth rate. Economic growth is the increase in Gross Domestic Product (GDP) of real continuous sourced from within the region. Local Government authorities to leverage the potential of local finance in local revenue as a form of decentralization. In addition to local revenue, the expenditure also affect economic growth. Spending the area in question in this research is capital expenditure. This research was conducted to determine whether the independent variable is local revenues have an impact on Gross Domestic Product (GDP) and capital expenditures. The data use in this research is a secondary data that obtained from the Central Statistics Agency of Bali, which is and then analyzed with multiple linear analysis method of intervening variables.The results showed a positive and significant effect of local revenue on capital expenditures and (GDP), capital expenditures no significant effect on GDP, and local revenue has no significant effect on GDP through capital expenditures.
Keywords: local revenue, GDP, and capital expenditures